Tribute to Josef Michl - Igor Alabugin; Petr Klán (Chemistry, 2021)
It is our great pleasure to introduce the Festschrift of Chemistry to honor professor Josef Michl (Figure 1) on the occasion of his 80th birthday and to recognize his exceptional contributions to the fields of organic photochemistry, quantum chemistry, biradicals and biradicaloids, electronic and vibrational spectroscopy, magnetic circular dichroism, silicon and boron chemistry, supramolecular chemistry, singlet fission, and molecular machines [...]